Control of central paleo-uplift on reservoir development of the fifth member of Majiagou Formation in Fuxian area - SU Juan,YANG Fei,ZHANG Juntao,ZHANG Tao,LIU Lu,YANG Jiaqi (Youqicang pingjia yu kaifa)
Since the discovery of the Ordovician weathering crust gas reservoir in the Ordos Basin in 1989, there has been notable progress in exploring the gas reservoir within the fifth member of the Majiagou Formation. However, the impact of the central paleo-uplift on the Majiagou Formation's deposition and reservoir characteristics in the Fuxian area remains underexplored. This gap in knowledge hampers oil and gas exploration efforts in the Lower Paleozoic strata of this region. Research into the stratigraphy, sedimentary microfacies, and karst development patterns of the Ordovician Majiagou Formation in the Fuxian area has shed light on how the central paleo-uplift influenced the area's geological deposition. This influence extends to the distribution of lithofacies and sedimentary microfacies as well. Findings indicate that the central paleo-uplift's effects on the Majiagou Formation in the Fuxian area have a legacy, with the formation's thickness varying significantly across different directions-thicker in the north and east, and thinner in the south and west. Further analysis of sedimentary microfacies reveals that the edges of the paleo-uplift were areas of strong hydrodynamic activity, leading to the formation of sheet-like intra-platform and tidal marginal beaches. The development of the Ordovician weathering crust is intricately linked to the central paleo-uplift's shape, structure, evolutionary history, and preservation conditions. The evolution of this uplift played a crucial role in both the development and preservation of the Ordovician karst system.